(untitled) (CIPEEX, 2025)
Botulinum toxin is one of the most widely used agents in aesthetic medicine, especially in facial procedures. Its ability to modulate muscle activity has made it a safe and effective tool for the treatment of dynamic wrinkles and facial rejuvenation. This narrative review aims to summarize the mechanisms of action, clinical indications, safety considerations, and aesthetic outcomes of botulinum toxin in facial practice. Recent articles indexed in PubMed and Scielo were analyzed to provide an updated overview of evidence-based applications. Results indicate that botulinum toxin contributes to wrinkle reduction, facial harmony, and patient satisfaction, with low incidence of adverse effects when performed by trained professionals. Advances in application techniques and dilution protocols have further improved precision, durability, and natural results. In conclusion, botulinum toxin remains a cornerstone in minimally invasive facial aesthetics, combining scientific support with clinical practice to achieve predictable and safe outcomes.